2021
DOI: 10.5267/j.msl.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotional intelligence on organizational commitment: Understanding the mediating role of job satisfaction

Abstract: This study aims to analyze how emotional intelligence (EI) influences organizational commitment along with the correlation between job satisfaction and these two aspects. To collect the data for this study, a polite and pre-validated, self-structured questionnaire was used. Additionally, ethical issues were considered with the assurance of anonymity. The study also took the convenience sampling approach and collected samples from customer service employees working in all main branches of Saudi banks located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 1 publication
3
28
0
1
Order By: Relevance
“…Previous research conducted by Dewi & Riana (2020), Adhiyasa & Satrya (2021), and Alsughayir (2021) have determined that work satisfaction plays a mediating role in the relationship between emotional intelligence and organizational commitment. They suggest that work satisfaction mediates the effect of emotional intelligence on organizational commitment.…”
Section: Work Engagement Mediates the Relationship Between Emotional Intelligence And Organizational Commitmentmentioning
confidence: 94%
“…Previous research conducted by Dewi & Riana (2020), Adhiyasa & Satrya (2021), and Alsughayir (2021) have determined that work satisfaction plays a mediating role in the relationship between emotional intelligence and organizational commitment. They suggest that work satisfaction mediates the effect of emotional intelligence on organizational commitment.…”
Section: Work Engagement Mediates the Relationship Between Emotional Intelligence And Organizational Commitmentmentioning
confidence: 94%
“…Past research demonstrated linear effects of leadership types, satisfaction at work, and employees' commitment towards their organisations (Abouraia & Othman, 2017). A recent study reported that job satisfaction mediated between work stress variables and organisational commitment (Alsughayir, 2021). However, there is no study on the role of job satisfaction as a mediator between leadership and organisational commitment of teachers.…”
Section: Introductionmentioning
confidence: 99%
“…In the future it may lead to an excess of terms and cause confusion. In general, it can be said that emotional intelligence is the ability to understand and manage one's own and others' feelings (Alsughayir, 2021(Alsughayir, : 1310(Alsughayir, -1311. Since the last century, many authors have written papers on a number of issues of emotional intelligence and have begun to focus on it in terms of human resource management, however, the main practical value of emotional intelligence is success in social relationships or careers.…”
Section: The Essence Of Emotional Intelligencementioning
confidence: 99%